1980
DOI: 10.1164/arrd.1980.122.5.794
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effect on Lung Function of Smoking Filtered and Nonfiltered Cigarettes1

Abstract: We measured and compared the effect of smoking a filtered and a nonfiltered cigarette on instantaneous maximal expiratory flow rates (Vmax50 and Vmax25) and airway resistance (Raw). We found a significant increase in Raw after both cigarettes, and a small decrease in Vmax50 after smoking the nonfiltered cigarette. The change in Vmax50 after smoking the filtered cigarette was not significant. We suggest, on the basis of these data, that filtered cigarette smoke reduces some of the constituents that cause bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(33 reference statements)
2
2
1
Order By: Relevance
“…Recently similar results were ob tained after smoking a filtered cigarette with low tar and nicotine content [8]. We postulated that this late bronchodilation could be due to release of cathecolamines by sympathetic ganglia and adrenal medulla (nicotine) or to some unknown component of tobacco.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Recently similar results were ob tained after smoking a filtered cigarette with low tar and nicotine content [8]. We postulated that this late bronchodilation could be due to release of cathecolamines by sympathetic ganglia and adrenal medulla (nicotine) or to some unknown component of tobacco.…”
Section: Discussionsupporting
confidence: 67%
“…This stems from the convic tion that the response to cigarette smoke is an 'irritant' response, mostly mediated through some particulate matter [1,2,21]. In a recent study of airway response to identical cigarettes, one filtered, one unfil tered, we showed a greater increase in air way resistance after smoking the high tar cigarette [8]. The present study, however, shows that the cigarette which caused a sig nificantly different response had an excep tionally low nicotine content.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Therefore, we postulated that the effect on the FEF50 was consistent with the constriction of the large and central airways because at this lung volume the airways resistor includes lobar and segmental bronchi [3,7].…”
Section: Introductionmentioning
confidence: 86%